2022
DOI: 10.1002/jcla.24361
|View full text |Cite
|
Sign up to set email alerts
|

Screening and identification of biomarkers associated with the immune infiltration of intracerebral hemorrhage

Abstract: Background Recent studies showed that inflammation and immunity might play essential roles in the progression of intracerebral hemorrhage (ICH). However, the underlying mechanisms for changes at the cellular and molecular levels after ICH remain unclear. Methods We downloaded the microarray dataset of ICH from the Gene Expression Omnibus (GEO) database. The differential expression gene analysis was obtained by weighted gene co‐expression network analysis (WGCNA). We got the hub genes and performed the biologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 44 publications
1
7
0
Order By: Relevance
“…Gene mutation profiling of patients with intracerebral haemorrhage has identified biomarkers associated with haemorrhage progression; however, these have not been explored in MDS-related bleeding. 23 Our study, similar to the Canadian audit, 17 demonstrated there is variation in clinical practice for patients with severe thrombocytopenia (platelet count <20 Â 10 9 /L); in our cohort, 32% received outpatient platelet transfusions alone, 25% received both platelet transfusions and TXA, 18% received TXA alone and 25% not on treatment. A recent Dutch clinical practice survey similarly found clinical practice variation; for MDS patients on hypomethylating agents, 87%…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…Gene mutation profiling of patients with intracerebral haemorrhage has identified biomarkers associated with haemorrhage progression; however, these have not been explored in MDS-related bleeding. 23 Our study, similar to the Canadian audit, 17 demonstrated there is variation in clinical practice for patients with severe thrombocytopenia (platelet count <20 Â 10 9 /L); in our cohort, 32% received outpatient platelet transfusions alone, 25% received both platelet transfusions and TXA, 18% received TXA alone and 25% not on treatment. A recent Dutch clinical practice survey similarly found clinical practice variation; for MDS patients on hypomethylating agents, 87%…”
Section: Discussionsupporting
confidence: 75%
“…Further, though IPSS‐R score did not predict bleeding risk in this cohort, we did not have data on gene mutation profiling due to the study period being prior to routine use of next‐generation sequencing. Gene mutation profiling of patients with intracerebral haemorrhage has identified biomarkers associated with haemorrhage progression; however, these have not been explored in MDS‐related bleeding 23 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Once the released blood components infiltrate into the parenchyma, an immediate inflammatory response is followed via mobilized and activated inflammatory cells [ 60 ]. Microglia, as the primary immune cell source of the innate immune system, participate in the pathological process of ICH and response to neuroinflammation [ 61 , 62 ].…”
Section: Discussionmentioning
confidence: 99%
“… 44 Microglia, as a key component in the innate immune system of brain tissue, can swiftly mobilize and activate in response to ICH-induced brain damage. 45 , 46 The abundance of M1 microglia cells can lead to neuronal damage via the secretion of pro-inflammatory cytokines and neurotoxic chemokines. Studies have demonstrated that MSCs possess the capability to induce the polarization of macrophages/microglia towards an M2 phenotype in CNS diseases by suppressing the secretion of inflammatory factors from microglia cells.…”
Section: Discussionmentioning
confidence: 99%